PENGARUH INFLUENCER MARKETING DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN DI PLATFORM E-COMMERCE DENGAN BRAND IMAGE SEBAGAI MEDIASI PADA TIKTOK SHOP - Shilfiyana, Dhindha; Miswanto, Miswanto; Biyanto, Frasto; Siregar, Baldric (Sekolah Tinggi Ilmu Ekonomi SBI, 2025)
This research examines the impact of Influencer Marketing and Word of Mouth (WOM) on purchasing decisions on the TikTok Shop e-commerce platform, with Brand Image as a mediating variable. The study utilizes a sample of 210 respondents, selected using purposive sampling, who have purchased products on TikTok Shop at least once. Data were collected through questionnaires distributed via social media and analyzed using the Structural Equation Modeling (SEM) method with SmartPLS 4.0 software. The results show that Influencer Marketing and WOM significantly influence purchasing decisions and Brand Image. Furthermore, Brand Image significantly mediates the relationship between Influencer Marketing, WOM, and purchasing decisions. The findings emphasize the critical role of Influencer Marketing and WOM in enhancing Brand Image and encouraging purchasing decisions among consumers. The research highlights that WOM has a more substantial impact on Brand Image than Influencer Marketing, showcasing its effectiveness as a strategy in shaping consumer perceptions.